2004
DOI: 10.1007/s10266-004-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotection of the murine submandibular gland by isoproterenol: autoradiography study with 3H-leucine

Abstract: Irradiation of the salivary glands results in the generation of free radicals from metal ions present in the secretory granules of acinar cells, a process that is believed to exacerbate radiation damage to the salivary glands. We therefore conducted a comparative investigation of radiation damage to the acinar cells of murine submaxillary glands in which granule secretion had been induced, and used autoradiography to visualize the pathological changes. Male BALB/c mice, at 8 weeks of age, were divided into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, a delay in absorbed 3 H-leucine release was observed in the nonIPR/10Gy group. In another study that used LMARG for cell observation, IPR administration was found to reduce the influence of irradiation on the acinar cells of the mouse submandibular gland 22 . However, the LMARG data did not indicate the effect of IPR administration.…”
Section: Discussionmentioning
confidence: 97%
“…However, a delay in absorbed 3 H-leucine release was observed in the nonIPR/10Gy group. In another study that used LMARG for cell observation, IPR administration was found to reduce the influence of irradiation on the acinar cells of the mouse submandibular gland 22 . However, the LMARG data did not indicate the effect of IPR administration.…”
Section: Discussionmentioning
confidence: 97%